Cytotoxic and genotoxic effects of two hair dyes used in the formulation of black color - Tafurt-Cardona, Yaliana [UNESP]; Suares-Rocha, Paula [UNESP]; Fernandes, Thaís Cristina Casimiro [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier B. V., 2015)
According to the International Agency for Research on Cancer (IARC), some hair dyes are considered mutagenic and carcinogenic in in vitro assays and exposed human populations. Epidemiological studies indicate that hairdressers occupationally exposed to hair dyes have a higher risk of developing bladder cancer. In Brazil, 26% of the adults use hair dye. In this study, we investigated the toxic effects of two hair dyes, Basic Red 51 (BR51) and Basic Brown 17 (BB17), which are temporary dyes of the azo group (R-N=N-R'), used in the composition of the black hair dye. To this end, MTT and trypan blue assays (cytotoxicity), comet and micronucleus assay (genotoxicity) were applied, with HepG2 cells. For cytotoxic assessment, dyes were tested in serial dilutions, being the highest concentrations those used in the commercial formula for hair dyes. For genotoxic assessment concentrations were selected according to cell viability. Results showed that both dyes induced significant cytotoxic and genotoxic effects in the cells, in concentrations much lower than those used in the commercial formula. Genotoxic effects could be related to the azo structure present in the composition of the dyes, which is known as mutagenic and carcinogenic. These results point to the hazard of the hair dye exposure to human health.
Keywords: Basic brown 17; Basic red 51; Comet assay; Micronucleus; Temporary hair dye